Efeitos de rejeitos de mineração de ferro sobre a diatomoflora perifítica na bacia do Rio Doce – MG - Ivan Menezes Monteiro (2020)
The Fundão tailings dam spill, occurred in the municipality of Mariana in Minas Gerais state (SE, Brazil), released approximately 39 million cubic meters of iron ore mine tailings in the Doce river basin. The discharged tailings from the breach event flowed down the courses of Santarém stream, Gualaxo do Norte river, Carmo river and Piranga river, impacting the entire length of the main channel and adjacent areas of the Doce river from its origin, in the state of Minas Gerais, to its estuary on the coast of Espírito Santo state. Watercourses affected by the breach changed their physical and chemical characteristics, with repercussions over the biota of these ecosystems. The present study assessed, through ecotoxicological tests in Nitzschia palea (Kutzing) W. Smith and spatial evaluation of the structure and taxonomic composition of periphytic diatom assemblage as proxy of the effects of the tailings over the aquatic community from stretches of Doce River Basin, relating them to abiotic variables. The exposure of Nitzschia palea invidious to the tailings leads to a reduction in chloroplast area, an increase in lipid volume and a reduction of cell motility. The results of spatial variation on the structure and composition of diatoms assemblages indicate the watercourses differed both concerning to the abiotic and biotic factors. Both richness and diversity of species were higher in environments not affected by the disruption. The assemblage taxonomic composition was different among the evaluated segments. Segments impacted by the tailings showed a greater abundance of resistant organisms. The results expressed here demonstrate that although being classified as non-hazardous, the tailings presents deleterious effects on diatoms, one of the major primary producers in aquatic ecosystems.